2016
DOI: 10.18203/2320-6012.ijrms20162878
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of levobupivacaine with ropivacaine for supraclavicular brachial plexus block

Abstract: INTRODUCTIONRecently peripheral nerve block anaesthesia has become popular against general anaesthesia as it is devoid of side effects of intubation and muscle relaxants and systemic haemodynamic changes. This type of anaesthesia is particularly advantageous in case of prolonged orthopedic, plastic reconstructive surgeries and in emergency surgeries where the patients are full stomach, not adequately starving and in high risk patients. This technique not only provides anaesthesia but also postoperative analges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…Our observations are in accordance with the findings of Mageswaran R et al [5] (2010), who observed the mean onset time (SD) for sensory blockwithropivacaine was 13.5±2.9 minutes compared to levobupivacaine at 11.1±2.6 minutes (p = 0.003). Similar results were found in the study by Kulkarni SB et al [6] (2016), who observed the onset of sensory blockade was rapid (8.6±1.522) minutes in levobupivacaine group than in ropivacaine group (9.533±1.656) minutes which was statistically significant (p value =0.027).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our observations are in accordance with the findings of Mageswaran R et al [5] (2010), who observed the mean onset time (SD) for sensory blockwithropivacaine was 13.5±2.9 minutes compared to levobupivacaine at 11.1±2.6 minutes (p = 0.003). Similar results were found in the study by Kulkarni SB et al [6] (2016), who observed the onset of sensory blockade was rapid (8.6±1.522) minutes in levobupivacaine group than in ropivacaine group (9.533±1.656) minutes which was statistically significant (p value =0.027).…”
Section: Discussionsupporting
confidence: 90%
“…Mean duration of sensory block was significantly prolonged in group L (12.07±1.09) hours as compared to group R (10.840±1.713) hours which is statistically significant with p value < 0.05. Our observations are in accordance with the findings of Prerana P Mankad et al [7] (2016) observed the duration of sensory blockade wassignificantly prolonged (10.93±1.363) hours in levobupivacaine group than in ropivacaine group (8.67±1.093) hours which was statistically significant ( p value <0.001) Similar results were found by Kulkarni SB et al [6] (2016), who observed the duration of sensory blockade was significantly prolonged (12.116±0.715) hours in levobupivacaine group than in ropivacaine group (11.266±0.751) hours which was statistically significant ( p value=0.0001).…”
Section: Mudgal and Saini: Brachial Plexus Block For Elective Upper Limsupporting
confidence: 93%
“…Next in order of efficiency are high-dose opioids, epidural opioids & clonidine, patientcontrolled opioid therapy, & NSAIDs. [8] Supraclavicular brachial plexus block is ideal for its rapid onset, reliable anesthesia & as a secure technique for any surgery in the upper extremity not involve the shoulder. This is because the block is performed at nerve trunks where almost the entire innervations of the upper extremity are confined to a very small surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Upper limb surgeries are mostly performed under peripheral blocks such as brachial plexus blocks. Peripheral nerve blocks not only provide intraoperative anaesthesia but also extend analgesia in the post-operative period without any systemic side-effects [1] . Supraclavicular brachial plexus block has been the choice of anaesthesia for upper limb surgeries over the past several decades.…”
Section: Introductionmentioning
confidence: 99%